2002
DOI: 10.1046/j.1365-2230.2002.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Male androgenetic alopecia

Abstract: Androgenetic alopecia (AGA) is the most common type of hair loss in men. The relative strong concordance of the degree of baldness in fathers and sons is not consistent with a smiple Mendelian trait and a polygenic basis is considered to be most likely. So far the predisposing genes for AGA are unknown and we do not understand the molecular steps involved in androgen-dependent beard growth versus androgen-dependent hair loss, but AGA can be defined as a DHT-dependent process with continuous miniaturization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 48 publications
1
36
0
7
Order By: Relevance
“…In the pathogenesis, it requires an adequate presence of androgens and a genetic predisposition. In the balding scalp, a miniaturization of genetically programmed hair follicles is driven by an increased uptake, metabolism and conversion of testosterone to dihydrotestosterone (DHT) by 5α-reductase [2, 3]. In men with AGA, hair loss occurs in the frontotemporal and vertex regions of the scalp.…”
Section: Introductionmentioning
confidence: 99%
“…In the pathogenesis, it requires an adequate presence of androgens and a genetic predisposition. In the balding scalp, a miniaturization of genetically programmed hair follicles is driven by an increased uptake, metabolism and conversion of testosterone to dihydrotestosterone (DHT) by 5α-reductase [2, 3]. In men with AGA, hair loss occurs in the frontotemporal and vertex regions of the scalp.…”
Section: Introductionmentioning
confidence: 99%
“…2 Lower prevalence has been seen among Asian, Native American, and African American men, whereas high prevalence has been found among men of white race/ethnicity. 3 The changes of AGA are androgen dependent and follow an inheritance mode with gene polymorphisms. 3 To our knowledge, only 1 gene that encodes the androgen receptor has been identified.…”
mentioning
confidence: 99%
“…3 The changes of AGA are androgen dependent and follow an inheritance mode with gene polymorphisms. 3 To our knowledge, only 1 gene that encodes the androgen receptor has been identified. 4 While prerequisites are androgens and a genetic predisposition, clinical practice has shown that simply blocking androgens does not result in the conversion of miniaturized follicles to terminal ones in advanced alopecia.…”
mentioning
confidence: 99%
“…Other known and validated factors influencing the development of common baldness are few but include polygenic inheritance patterning, higher levels of 5-alpha reductase, which is responsible for converting testosterone into a more potent androgen, and aging (Hamilton, 1951;Hoffman, 2002;Price, 2003;Severi et al, 2003;). Many women with alopecia, however, have normal levels of circulating androgens.…”
Section: Discussionmentioning
confidence: 99%